Gearing Service Quality into High Educational Institutes in Cambodia - Ung, Veasna; Norng, Tha (Archives of Business Research, 2017)
In the challenging atmosphere of globalization era, the educational quality has not only become a major industry and need of the day but it is also an investment by the parents for their children. This quality focus on excellent learning process and public satisfaction on the service offered and it is bridge to attract and keep students who want to get universities in public sector as well as in private sector. Measuring student satisfaction is key point in determining service quality at higher educational institute. The main purpose of this paper is to evaluate students’ satisfaction on services provided by universities in Cambodia. Specifically, the study found significant relationship between the five dimensions of augmented SERVQUAL (tangibility, reliability, assurance, technology, empathy, and responsiveness) or TRATER and students’ satisfaction. Data was collected from 1368 students from both public and private sector universities/institutes are included in this study. The estimation results show that five dimensions (TREAT dimension: tangibility, responsiveness, empathy, assurance, and technology) have a significant, positive impact on the overall student satisfaction (OSS), with empathy being the most important predictor of student’s satisfaction. Recommendations and implications for policy makers are discussed and guidelines for future research are also provided. Such discovery should help universities to conduct better strategic plan to meet students’ satisfaction in particular and its overall performance in general.